The Influence of Health Beliefs, of Resources, of Vaccination History, and of Health Anxiety on Intention to Accept COVID-19 Vaccination - Ştefănuţ, Adelina Mihaela; Vintilă, Mona; Tomiţă, Mihaela; Treglia, Eugenia; Lungu, Monica Alina; Tomassoni, Rosella (Frontiers in Psychology, 2021)
The aim of this study is to investigate whether Health Belief Model constructs, personal resources, vaccination history and health anxiety exert an influence on vaccination intention. To achieve this end, we carried out a cross-sectional study of 432 people drawn from a convenience sample who answered an online questionnaire. Multiple logistical regressions showed that perception of the severity of the disease, of the benefits of being vaccinated, of barriers, and of cues to action, along with the freeness and accessibility of the vaccine and general vaccination history, are significant predictors regarding vaccination intention.